Hybrid scheme for the prediction of microstructural features of ferritic stainless steel welds - Amuda, Muhammed Olawale Hakeem; Mridha, Shahjahan (2010)
There is an increasing use of predictive tools in modeling microstructural features of welds towards eliminating weld defects and optimizing mechanical properties. Significant attraction in these tools is that they forecast weld character from a variety of process parameters and thus ensure the production of tailored weld microstructure with improved mechanical properties. In this paper, a further attempt at enhanced prediction of microstructural features of ferritic stainless steel weld is proposed. The model involves a composite scheme of finite element analysis and artificial intelligence modules. Current predictive schemes are based on exclusive two-step algorithm utilizing decomposition kinetics. The proposed model is an integrative algorithm that speeds up the prediction process with better flexibility and eliminates the needs for reaction kinetics.